2014
DOI: 10.5539/ass.v10n5p71
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Social Skills through Outdoor Education and Assessing Its’ Effects

Abstract: Outdoor education is a holistic form of education which aids in overall wellbeing of adolescence, including academic, physical, emotional, social and psychology well being. The aim of this study was to see whether outdoor education promotes social skills and assess its effects on participants. Research sample comprised of 671 adolescence attending a five-day residential outdoor education program. Kolb's Cycle of Learning through Experience is used as the theoretical framework while the research framework is ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 9 publications
1
12
0
3
Order By: Relevance
“…The conclusions of the research performed by Harun and Salamuddin (2014) confirmed that empiric learning during the physical activity is basis of the development of social capabilities. The works of other scientists (Del Val Núñez, Romero, Sánchez, & Aránega, 2018;Muñoz Campos, 2017) also confirm the development of social capabilities during empiric learning.…”
Section: Resultssupporting
confidence: 53%
“…The conclusions of the research performed by Harun and Salamuddin (2014) confirmed that empiric learning during the physical activity is basis of the development of social capabilities. The works of other scientists (Del Val Núñez, Romero, Sánchez, & Aránega, 2018;Muñoz Campos, 2017) also confirm the development of social capabilities during empiric learning.…”
Section: Resultssupporting
confidence: 53%
“…Teachers, parents, and students report that wilderness and other nature experiences boost self-confidence, critical thinking, and problem-solving (e.g., Kochanowski and Carr, 2014; Truong et al, 2016) as well as leadership and communication skills such as making important decisions, listening to others, and voicing opinions in a group (e.g., Jostad et al, 2012; Cooley et al, 2014). Students emerge more resilient, with a greater capacity to meet challenges and thrive in adverse situations (Beightol et al, 2012; Cooley et al, 2014; Harun and Salamuddin, 2014; Warber et al, 2015; Richmond et al, 2017). Interestingly, greener everyday settings may also boost positive coping (Kuo, 2001) and buffer children from the impacts of stressful life events (Wells and Evans, 2003).…”
Section: Outcomes For Learning and Developmentmentioning
confidence: 99%
“…The concept outdoor itself refers to open-air settings (English Oxford Living Dictionaries). Outdoor education comprises a holistic form of education with the goal of enhancing the overall well-being of children and adolescents, including their academic, physical, emotional, social, and psychological well-being (Harun & Salamuddin, 2014). The conceptual jungle in the field is evident.…”
Section: Definition: What Is Outdoor Education?mentioning
confidence: 99%
“…These aspects all contribute to the social and psychological well-being of children. Indeed, another important benefit of outdoor education is the promotion of social relationships and the practice of social skills in group settings (Harun & Salamuddin, 2014), thereby increasing the meaningfulness of this approach from students' perspectives (see also Garrison, Östman, & Håkansson, 2015).…”
Section: Outdoor Education As a Meaningful Learning Experiencementioning
confidence: 99%